2021
DOI: 10.1002/cjp2.245
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic implications of a three‐antibody molecular subtyping algorithm for non‐muscle invasive bladder cancer

Abstract: Intrinsic molecular subtypes may explain marked variation between bladder cancer patients in prognosis and response to therapy. Complex testing algorithms and little attention to more prevalent, early-stage (non-muscle invasive) bladder cancers (NMIBCs) have hindered implementation of subtyping in clinical practice. Here, using a three-antibody immunohistochemistry (IHC) algorithm, we identify the diagnostic and prognostic associations of well-validated proteomic features of basal and luminal subtypes in NMIBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 53 publications
(130 reference statements)
0
28
0
Order By: Relevance
“…Conversely, other subtyping schemes, including the Lund taxonomy and the recent consensus molecular classification, suggested that the Lum group may be further split into subgroups with peculiar biological and prognostic features [ 13 , 83 , 84 ]. Both Uro and GU express urothelial differentiation markers GATA3 and FOXA1 while lacking basal markers CK5 and CK14 [ 85 , 86 ], yet differ with regard to the mechanisms of cell cycle checkpoint inactivation [ 25 ]. Uro cancers inactivate the cell cycle regulator RB1 indirectly through loss of CDKN2A, which encodes the p16INK4A cyclin-dependent kinase inhibitor [ 87 , 88 ] and may be further split into UroA and UroB.…”
Section: Ihc-based Molecular Subtypesmentioning
confidence: 99%
See 3 more Smart Citations
“…Conversely, other subtyping schemes, including the Lund taxonomy and the recent consensus molecular classification, suggested that the Lum group may be further split into subgroups with peculiar biological and prognostic features [ 13 , 83 , 84 ]. Both Uro and GU express urothelial differentiation markers GATA3 and FOXA1 while lacking basal markers CK5 and CK14 [ 85 , 86 ], yet differ with regard to the mechanisms of cell cycle checkpoint inactivation [ 25 ]. Uro cancers inactivate the cell cycle regulator RB1 indirectly through loss of CDKN2A, which encodes the p16INK4A cyclin-dependent kinase inhibitor [ 87 , 88 ] and may be further split into UroA and UroB.…”
Section: Ihc-based Molecular Subtypesmentioning
confidence: 99%
“…Jackson et al reported that the GATA3+/P16−/CK5− Uro NMIBCs had earlier recurrences post-BCG treatment as compared to GATA3+/P16+/CK5− GU tumors [ 25 ]. Deep deletion or loss of chromosome 9p, including the CDKN2A locus, which encodes P16, is a recurrent alteration in early BCs [ 11 , 23 , 37 , 90 ], whereas GU NMIBCs do not show changes in CDKN2A nor in p16 protein expression [ 23 , 37 ].…”
Section: Ihc-based Molecular Subtypesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the p16 assay used in the studies analyzed here showed a lower dynamic range than an assay used in subsequent work. 31 Thus, implementing this classifier will require normalizing differences in dynamic range between assays and centers, including necessary control tissues.…”
Section: Discussionmentioning
confidence: 99%